The Effect of Early Ambulation on Postoperative Elderly: A Systematic Review - Susana Susana; Etty Rekawati; Junaiti Sahar; Yossie Susanti Eka Putri (GLOBAL HEALTH SCIENCE GROUP, 2025)
Elderly patients face various surgical risks, including complications, slower recovery, prolonged hospital stays, functional decline, and even death. Early ambulation is beneficial in reducing these risks in older adults. However, elderly patients often lack motivation to ambulate due to insufficient understanding and family support, leading to longer bed rest. Aim : To evaluate the impact of early ambulation as an intervention to enhance postoperative recovery in elderly patients. Methods: This is a systematic review study with a PICO approach. Article searches were conducted using online databases such as EBSCO, PubMed, ScienceDirect, SpringerLink, and Scopus with the keywords (Elderly OR Older Adult) AND (Post Operative OR Post Surgery) AND (Early Ambulation OR Early Mobilization) AND (Reduce Length of Stay) published between 2014–2024 and The 5 relevant articles were found. Results: Five studies indicated that the implementation of early ambulation programs in elderly surgical patients not only reduces length of stay but also improves functional capacity and decreases the incidence of complications such as pneumonia, atelectasis, and venous thrombosis. Conclusion: The studies show that early mobilization reduces hospital stays, accelerates organ function recovery, and provides psychological benefits, such as reduced postoperative anxiety.